Patterns of Response and Remission Following a One-Session Treatment for Blood-Injection-Injury Phobia in Youth. Issue 1 (2nd January 2017) - Oar, Ella L.; Farrell, Lara J.; Conlon, Elizabeth G.; Waters, Allison M.; Ollendick, Thomas H.
ABSTRACT: Blood-Injection-Injury (BII) Phobia is a severe and impairing disorder that has been understudied in youth. The present study aimed to define patterns of response and remission following a modified One-Session Treatment (OST) including an e-therapy maintenance program for children and adolescents with BII Phobia. Moreover, characteristics of different responder groups were examined in order to determine correlates of a poorer response. Youth ( n = 20; 8–18 years) were categorized into four responder groups (e.g., immediate remitter, delayed remitter, partial responder, and nonresponder) based upon defined criteria for remission. Immediate remitters to treatment were more likely to have a primary diagnosis of injection phobia, rather than a combined blood and injection phobia. Nonresponders reported significantly greater disgust sensitivity at pretreatment and were more likely to have a comorbid diagnosis of Social Phobia. In regards to within session change, youth who achieved the exposure goal of having a blood test during treatment had a significantly stronger treatment response. These preliminary findings may assist clinicians in the planning and delivering of intensive Cognitive Behavioral Treatment (CBT) approaches for BII Phobia in youth.